A quality improvement initiative on the management of osteoporosis in older people with Parkinsonism. Issue 1 (25th October 2016) - Singh, Inderpal; Fletcher, Rachel; Scanlon, Linda; Tyler, Mandy; Aithal, Shridhar
Abstract : The risk of falls is higher in patients with people with Parkinsonism (PwP) compared to those without Parkinsonism, and leads to adverse outcomes including fragility fractures. Osteoporosis is under-recognised, and the prevalence of fragility fractures in not well studied. The primary aim of this project is for 100% of new patient referrals to, and 80% of follow up patients within the movement disorder (MD) service with osteoporosis to be treated in accordance with evidence based osteoporosis guidance. Routinely captured information regarding demographics and fragility fractures was retrospectively extracted from the clinical workstation, clinic letters, and clinical coding between July and November 2015. The prevalence of fragility fracture was 22.6% (68/300), and only 40% (27/68) were on appropriate treatment for osteoporosis. A quality improvement (QI) methodology based on the model of improvement, Plan-Do-Study-Act (PDSA) cycles were used, and a monthly multidisciplinary team (MDT) meeting was introduced. This QI initiative has shown that MDT input can reduce referrals to physiotherapists; and also 100% of new patients, and 91% of follow up patients received evidence based osteoporosis treatment.